AB0559 The prevalence of non-criteria anti-phospholipid antibodies in anti-phospholipid syndrome. (12th June 2018) - Li, C.; Zhu, L.; Wang, Z.; Sun, Y.; Mu, R.; Li, Z.
Abstract : Background: Antiphospholipid syndrome (APS) is an autoimmune disease characterised mainly by arterial and/or venous thrombosis, recurrent pregnancy morbidity, with the presence of a variety of heterogeneous circulating antiphospholipid antibodies. However, there are a group of APS patients with persistently negative antiphospholipid antibodies. It is necessary to validate new specific antibodies to better recognition of these APS patients. Objectives: To explore the clinical significance of non-criteria anti-phospholipid antibodies in a large cohort of Chinese patients with anti-phospholipid syndrome (APS). Methods: Serum samples were obtained from 214 APS patients, 122 disease control including systemic lupus erythematosus, sjogren syndrome, ankylosing spondylitis, rheumatoid arthritis, osteoarthritis and 50 healthy control. Antiphosphatidylserine(IgA/IgG/IgM) (aPS), anti-phosphatidylethanolamine (IgA/IgG/IgM) (aPE), anti-prothrombin-antibodies (IgA/IgG/IgM) (aPT), anti-annexin V-antibodies (IgA/IgG/IgM) (aAnxV), anti-phosoholipid-antibody(IgG/IgM)(aPL), anti-oxLDL antibody(IgG/IgM)(aoxLDL) were tested by ELISA kits(HUMAN Diagnostics Products, Germany) and IgG/IgM APhL were tested by ELISA(Louisville APL Diagnostic, USA). The Chi-square (χ2) test was used to examine the difference of frequencies of antibodies in APS patients and patients with other diseases. Spearman correlation analysis was performed to investigate the relationship between aPS/PT and other clinical/laboratory parameters. Results: The prevalence of aPS IgG, aPS IgM, aPT, aPE, aAnxV, aPL, aoxLDL and IgG APhL, IgM APhL were 44.8%, 22.4%, 46.3%, 9.8%, 17.8%, 44.4%, 22.4%, 45.3% and 22.9%. The specificity of the antibodies were 82.6%, 95.3%, 96.0%, 99.4%, 95.3%, 92.4%, 87.2%, 95.3% and 94.8%. The highest positive predictive values of these antibodies were aPE. aPE, aPS IgM and APhL IgM were associated with thrombotic events and oxLDL, aPE, aPL, aPS IgG, aPS IgM, aPT, aoxLDL, APhL IgG and APHL IgM were correlated with anti-cardiolipin antibody(ACL). aPL, aPS IgG, aPS IgM, aPT, APhL IgG and APhL IgM were associated with β2-GP1 antibody. APhL IgG, APhL IgM and PS IgG were the highest prevalence in both ACL and lupus anticoagulant (LAC) negative patients. aPT has the highest prevalence in ACL and β2-GP1 negative patients and APhL IgG and aPS IgG were the highest two antibodies in LAC and β2-GP1 negative patients and aPT has the highest prevalence in seronegative APS patients. Conclusions: Non-criteria aPLs have a good diagnostic value in APS and were associated with thrombotic events. References: [1] Hughes GR, Khamashta MA (2003) Seronegative antiphospholipid syndrome. Ann Rheum Dis62:1127 [2] Examining the prevalence of non-criteria anti-phospholipid antibodies in patients with anti-phospholipid syndrome: a systematic review.Rheumatology2015;54:2042–2050. [3] A unique antiphospholipid assay recognizing phospholipid mixture compared with criteria antiphospholipid immunoassays in lupus patients. Lupus2017;26(6):606–615. Acknowledgements: We thank all patients and healthy donors whom took part in this study. Disclosure of Interest: None declared